Intra-operative methadone effect on quality of recovery compared with morphine following laparoscopic gastroplasty: a randomised controlled trial - Pontes, J. P.J.; Braz, F. R.; Módolo, N. S.P. [UNESP]; Mattar, L. A.; Sousa, J. A.G.; Navarro e Lima, L. H. (Wiley, 2020)
The effect of intra-operative intravenous methadone on quality of postoperative recovery was compared with morphine after laparoscopic gastroplasty. We included 137 adult patients with a body mass index > 35 kg.m−2 who underwent bariatric surgery. Patients were allocated at random to receive either intra-operative methadone (n = 69) or morphine (n = 68). All patients received the same postoperative care and analgesia. The primary outcome of postoperative quality of recovery was assessed using the Quality of Recovery-40 questionnaire total score 24 h after surgery. Secondary outcomes were assessed in the post-anaesthesia care unit the night of the day of surgery (T1), in the morning after surgery (T2); and at night on the day following surgery (T3). The median (IQR [range]) total Quality of Recovery-40 questionnaire score of 194 (190–197 [165–200]) was higher (p < 0.0001) in the methadone group compared with the score of 181 (174–185.5 [121–200]) in the morphine group. In the post-anaesthesia care unit, the pain burden; incidence of nausea and vomiting; rescue morphine dose; and time to discharge, were significantly lower in the methadone group. On the ward, the methadone group had a lower: incidence of rescue morphine requests at T1 (5.8 vs. 54.4%, p < 0.0001) and T2 (0 vs. 20.1%, p < 0.0001); and incidence of nausea (21.7 vs. 41.2%, p = 0.014), compared with the morphine group. We conclude that intra-operative intravenous methadone improved quality of recovery in patients who underwent laparoscopic gastroplasty, compared with intra-operative morphine. Methadone also reduced postoperative pain, postoperative opioid consumption and the incidence of opioid-related adverse events.
Keywords: bariatric surgery; methadone; morbid; obesity; patient reported outcome measures; quality measures: patient care